Effects of teacher licensing on educators' professionalism: UAE case in local perception. Issue 11 (November 2021) - Abdallah, Asma Khaleel; Musah, Mohammed Borhandden
Abstract: There is neither a universally recognized teacher licensure system, nor consensus on the criteria for assessing how teacher licensing programs affect the quality of teachers. This is the study to assess the licensing program impact on the professional qualities of UAE teachers. The perception survey was piloted with a group of teachers from random UAE schools. A survey method with valid tests and descriptive statistics were used to determine the self-evaluation of teachers in a wide range of competencies related to licensing. Teacher self-evaluate themselves during the test accentuates strong social competence, while professional qualities and professional growth received significantly lower scores. A strong direct correlation was found between test size and participants' experience. There was no correlation between the quality of the assessment and gender or age factors. The results of the study are aimed at helping government and academic policymakers to obtain feedback from teachers on educational reforms. Both the results of the study and the methods of its implementation can be expanded beyond the UAU due to the typological similarity of problems of licensing of teachers in different countries. The originality and novelty of the research is presented by the analysis of the subjective assessment of their results by teachers who passed licensing for the first time in the conditions of UAE, where the licensing system is in the process of formation. The findings of the study demonstrate the points of further development of the newly created teacher licensing system. Highlights: There is little relationship between the survey and gender, age and experience Older teachers normally have both a license and extensive teaching experience Attributes related to professional skills were scored significantly lower More critical and adequate self-perception is based on international experience Abstract : Educational policy; Licensing; Teacher perception; Teacher professionalism.